RISK ASSESSMENT OF SAFETY AND SECURITY OF BALI COASTAL AND ASSIGNMENT OF DENPASAR NAVAL BASE ELEMENTS - Astawa, Nyoman; Vanany, Iwan; Krisdiono, Eko; Mukhlis, Mukhlis (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2023)
The management of Bali's coastal waters is one of the priorities of the Bali provincial government as one of the drivers of the community's economy. The aspect of marine security and safety is one of the important factors that must be maintained to support the effective management of a waters. Therefore, mitigation measures are needed in dealing with various types of threats with the level of risk posed in the management of the Bali Coastal Sea waters. Denpasar Naval Base as one of the institutions tasked with maintaining security and safety in the territorial waters of Bali. The title of marine security operations element of the Denpasar Lanal is one of the main forces in maintaining security and safety stability in Bali's waters. In this research, identification of the types of threats and measurement of the risks posed will be carried out, which are measured from the perspective of maritime security and safety. From the results of the risk analysis, optimization modeling for the assignment of Denpasar Naval Base elements was carried out as a mitigation measure for various types of threats to be assigned to several Naval Post located in the coastal area of Bali. Identification of the types of threats is carried out by involving several experts in the field of maritime security and safety, measuring the value of risk is carried out using the Relative Comparison method. The assignment of Denpasar Naval Base elements is carried out using the Hungarian assignment method with the risk cost as a minimized aspect. The results of the risk assessment measurement show that the biggest risk faced in the management of the Bali Coastal is on the safety aspect of 67% and the security aspect with a proportion of 33%. The Assignment Optimization Model succeeded in optimizing the assignment of 6 (six) elements of the Denpasar Naval Base to 6 (six) Naval Post in the Bali Coastal Area. Keywords: Maritime Security and Safety, Risk Assessment, Hungarian Methods Assignment Model